The Use of Hume AI in Speaking Assessments: Teachers’ Perceptions in Senior High School Contexts - Nisa Fahria Nasution; Diah Safithri Armin (FOSTER: Journal of English Language Teaching, 2025)
This research aims to investigate the perception of teachers about the use of Hume AI for assessing students’ speaking skills in senior high school. English teachers (n=4) from public senior high schools in North Sumatra participated in this study. This research employed a descriptive qualitative method with semi-structured interviews and field note observations. The data was examined by using thematic analysis. The result indicated that Hume AI has a positive impact on students’ enthusiasm and interest. However, several challenges hinder the optimal use of Hume AI in speaking assessments, particularly in spontaneous speaking, including their low motivation to learn English due to socio-economic factors, and insufficient access to technological infrastructure within schools. Despite these obstacles, teachers acknowledged the potential of Hume AI to enhance speaking assessment and recommended its integration as both a learning and assessment tool. These findings offer insightful information for teachers, policymakers, and AI developers looking to implement AI-based tools in language learning and assessment practices.